Business Actor Liability for the Misuse of Company Secrets Obtained Through Collusion: A Study of KPPU Decision No. 08/Kppu-L/2024 - Irwan Bauw, Elirica Aliyah; Tarina, Dwi Desi Yayi (Al-Risalah, 2026)
This study analyzes the forms of business actors’ liability for the misappropriation of confidential information obtained through collusion under Article 23 of Law No. 5 of 1999, using the case of KPPU Decision No. 08/KPPU-L/2024 concerning PT Chiyoda Kogyo Indonesia as the focal point. The research employs a normative juridical method through statutory and case study approaches, applying a deductive–interpretative reasoning model to assess the consistency of legal norms and the construction of corporate liability in competition law enforcement. The findings indicate that the misappropriation of corporate secrets through collusion meets the elements of Article 23 under the rule of reason approach, as it generates anti-competitive effects such as lost sales, market structure distortions, and reduced competitive discipline. The KPPU panel applied identification theory and vicarious liability to attribute the actions of individuals to the corporation; however, the effectiveness of law enforcement is constrained by KPPU’s limited authority, which allows only administrative sanctions without personal liability. The novelty of this study lies in the integration of normative analysis, corporate liability theory, and a law-and-economics framework to assess the competitive impact of information collusion. The study has theoretical implications by reaffirming the position of corporate secrets as part of market structure and practical implications through recommendations for legal reform, including turnover-based fines and the expansion of KPPU’s authority to enhance deterrence and the effectiveness of competition law enforcement in Indonesia.